Pulmonary Hemodynamics and Six-Minute Walk Test Outcomes in Patients with Interstitial Lung Disease - Osamu Nishiyama; Ryo Yamazaki; Hiroyuki Sano; Takashi Iwanaga; Yuji Higashimoto; Hiroaki Kume; Yuji Tohda (Canadian Respiratory Journal)
Background. Six-minute walk test (6MWT) has 3 measurement outcomes, which are walk distance, desaturation, and symptom. The aim of this study was to examine whether routinely measured right-heart catheter (RHC) data correlate with 6MWT outcomes in patients with interstitial lung disease (ILD). Methods. Between June 2010 and December 2012, consecutive patients with ILD who underwent evaluation, including pulmonary function test, hemodynamic studies with right-heart catheter, and 6MWT as routine general practice, were recruited. Correlates of 3 outcomes of 6MWT were examined to reveal significant predictors. Results. Forty-six patients consisting of 20 with idiopathic pulmonary fibrosis, 14 with collagen vascular disease associated ILD, and 12 with other idiopathic interstitial pneumonia were recruited (mean % predicted FVC: 76.7±17.1%). Several physiological variables, including mean pulmonary artery pressure (PAP) and pulmonary vascular resistance (PVR), were correlated with each 6MWT outcome. Stepwise multivariate regression analyses showed that % predicted FVC and % predicted DLco were independent predictors of walk distance (r2=0.35, p=0.0002). For SpO2 at the end of 6MWT, % predicted DLco and PVR were selected as independent predictors (r2=0.46, p<0.0001). For dyspnea at the end of 6MWT, % predicted DLco was only one predictor (r2=0.18, p=0.005). Conclusion. Mean PAP had little impact on 6MWT outcomes in ILD patients who were nonselectively recruited, although PVR was one of predictors of desaturation.